CONSERVATION OF FISH MIGRATIONS AT HYDROELECTRIC POWER PLANTS: FISH PASSAGE SYSTEMS AS AN ENVIRONMENTALLY RESPONSIBLE MEASURE - Boštjan Pišotek; Sandra Velkovski (Journal of Energy Technology, 2025)
The geostrategic situation in the world is a stark reminder that, for any country seeking to be sovereign, it is essential to strengthen the degree of energy and food self-sufficiency as soon as possible, all the while also ensuring sustainable environmental and social development. In terms of renewable energy sources, Slovenia has the greatest privilege in being able to utilise hydropower and wood biomass for energy uses. The paper discusses the importance of implementing multipurpose and goal-oriented projects such as hydropower plants (HPPs), which fulfil a number of strategies set by the state and local communities. Since every human intervention in the environment has certain impacts, the paper shows how synergistic effects can be created between environmental protection and energy sector development through responsible environmental planning and implementation of the best possible measures, drawing from a practical example of the multipurpose construction project of HPPs on the lower course of the river Sava. The paper addresses the issue of fish migration and barriers in watercourses, presenting the current situation in Slovenia and worldwide. It also examines the success of fish passes at HPP Arto-Blanca, based on several years of monitoring. Such passes enable fish to migrate past hydropower plants, maintain healthy fish populations, preserve genetic diversity, and ensure the connectivity and preservation of the entire aquatic ecosystem. The example of the future Mokrice hydropower plant illustrates the trend and commitments in the planning of such passes in the future.